In the Aftermath: Consumer Choice and the Deregulation of Australian Retail Banking, 1988–1993. (30th September 2015) - Taylor, Judy; Magee, Gary
Abstract : This article explores whether deregulation of the Australian retail banking sector in the 1980s delivered the enhanced consumer choice that had been promised. Using new data on banking products and their usage, it analyses consumers' ability to select optimal 'frontier' products. It concludes that following deregulation of retail banking, product offerings underwent such tumultuous change that the scope for effective consumer choice was severely constrained. While there were improvements towards the end of the period, progress was not assisted by the banks' strategy of proliferating and re‐bundling products. Consequently, the anticipated improvements to consumer choice were slow to arrive.